A randomized controlled trial of a nurse-led psychological pain solution-focused intervention for depressed inpatients: study protocol - Shu-Yan Chen; Cheng Bian; Yin Cheng; Wei-Wei Zhao; Shi-Rui Yan; Yan-Hong Zhang (BMC Nursing, 2023)
Abstract Background Depressed patients commonly experience psychological pain. Research pointed to positive psychological interventions as an effective means of ameliorating psychological pain, although the exact effect is unclear. Based on the hope theory and solution-focused brief therapy (SFBT), this study combines hope theory with solution-focused brief therapy to develop a nurse-led psychological pain solution-focused (PPSF) intervention in depressed patients. Methods This is an assessor-blinded randomized controlled trial following the SPIRIT guidance. A total of 84 depressed patients will be recruited from the inpatient wards of a psychiatric hospital and randomly assigned to the control and experimental groups. Patients in the control group will be treated as usual. In contrast, patients in the experimental group will receive 6 sessions of the PPSF intervention for two weeks on top of the routine care. Primary outcomes are psychological pain, hope, cognitive distortions. Secondary outcomes are depression and suicidal ideation. Data will be collected at 5-time points: baseline, 1 and 2 weeks (post-intervention), 1 month (follow up), and 6 months after baseline. Generalized equation evaluation will be used to assess the effectiveness of the PPSF intervention. Discussion From a positive psychology perspective, there remains much room for developing psychological pain interventions in depressed patients. SFBT and hope theory are both based on positive psychology. With hope theory as the general framework and SFBT questions as the practical guide, the PPSF intervention program is designed that nursing staff can implement. If the intervention is effective, it will advance the development of psychological pain interventions for patients with depression. Trial registration ChiCTR2100048223